Evidence of horsemanship and dogmanship and their application in veterinary contexts. Issue 3 (June 2015) - Payne, E.; Boot, M.; Starling, M.; Henshall, C.; McLean, A.; Bennett, P.; McGreevy, P.
Highlights: This article reviews horsemanship and dogmanship in the veterinary sector. The arousal and affective state of the animal are useful determinants of best practice. Factors which define best practice have been identified and tabulated. Affiliation and positive reinforcement are crucial to horsemanship and dogmanship. Abstract: This review collates peer-reviewed evidence for desirable attributes for those who work with dogs and horses. It is written with a particular focus on the veterinary profession. Although veterinarians and veterinary nurses (VNs) occupy variable roles when interacting with their patients, several behavioural attributes emerge as helpful across the range of such roles. In light of recent research on the value of considering animals' arousal and affective state as predictors of behaviour and welfare, best practice in human–horse and human–dog-interactions is outlined. The attributes of affiliation, safety and positive reinforcement seem to contribute greatly to the development and maintenance of moderate arousal and positive affect in animals. The information in this review article is offered in an attempt to show why veterinary professionals with good horsemanship are likely to remain safe, and to introduce the concept of dogmanship. In the light of the peer-reviewed evidence assembled here, it is arguable that veterinary teams, comprising both veterinarians and VNs, can become scholars in these areas. The benefits of this approach for practitioner safety, animal welfare and client satisfaction are likely to be significant.